Book Review: There Goes the Neighborhood: Rural School Consolidation at the Grass Roots in Early Twentieth-Century Iowa - Paul Theobald (Journal of Research in Rural Education, 1999)
There Goes the Neighborhood is a well-researched addition to the body of existing literature dealing with rural educational history. Like Alan DeYoung's The Life and Death of a Rural American High School: Farewell Little Kanawha', the great strength of Reynolds' work is that it provides and historical "close-up" of how consolidation came to be sold to a rural community and the divisive debates that ensued. In There Goes the Neighborhood, Reynolds offers an engaging account of school consolidation in Delaware County, Iowa. This story, together with DeYoung's work in West Virginia, represents the best secondary sources available for historians who would like some leverage over "how it really happened" in the lives of rural people.